A centrifugal microfluidic pressure regulator scheme for continuous concentration control in droplet-based microreactors. Issue 22 (22nd October 2019) - Wang, Yuye; Liu, Shiyue; Zhang, Tiankai; Cong, Hengji; Wei, Yuanyuan; Xu, Jianbin; Ho, Yi-Ping; Kong, Siu-Kai; Ho, Ho-Pui
Abstract : A novel ratio-adjustable centrifugal droplet fusion platform dedicated to micro-reactor applications. Abstract : Droplet microfluidics is an emerging tool in many biological and chemical application areas such as digital polymerase chain reaction (PCR) and in vitro diagnosis because of its extremely small sample volume and wide range of possibilities for on-demand adjustment of droplet properties. Although centrifugal microfluidics has been reported as a viable scheme for droplet generation, there is not much progress as far as droplet manipulation and droplet-based reactions are concerned. In this paper, we report a microfluidic pressure regulator scheme along with the use of microcapillaries for periodic droplet generation and the subsequent fusion. This scheme enables fine control over droplet generation and the fusion process by varying the rotational frequency. To control the solution concentration in droplets, we have implemented several fusion devices, including one-to-one mode using a symmetric structure and ratio-adjustable mode with an asymmetric structure. As an application example, we performed cell transfection using the reported droplet-based technique, which resulted in considerable improvement in terms of transfection efficiency compared to the traditional bulk approach. In another example, we synthesized quasi-2D perovskites with controllable compositions and tunable photoluminescence peaks, thus confirming the volumetric accuracy of this approach down to the nano-liter scale. Compared to the common pressure pulsation approach, our centrifugal force actuation scheme offers the advantages of compactness and highly parallel batch processing. We anticipate that the new scheme will find many applications in cell biology and chemical synthesis.